Nanocrystalline electroplated NiFe‐based alloys for integrated magnetic microsensors. Issue 5 (25th February 2013) - Theis, Martin; Ediger, Simon; Schmitt, Martin Tobias; Hoffmann, Joachim‐Ernst; Saumer, Monika
Abstract The effect of pulse plating (PF) and direct current (DC) plating on the magnetic properties and grain size of electroplated NiFe films for the application in magnetic microsensors, i.e., as integrated magnetic concentrator, has been studied. In order to further improve magnetic properties additional subsequent thermal annealing experiments were carried out with chosen films. A sulphate‐based NiFe electrolyte containing various additives operated at a pH of 3.5 and a temperature of 50 °C was used. The softmagnetic NiFe films were deposited at a thickness of >10 µm on silicon substrates with a sputtered 200 nm thick Cu seed layer and a 50 µm high photoresist mould. The composition and magnetic properties were measured by energy dispersive X‐ray spectroscopy (EDX) and vibrating sample magnetometer (VSM), respectively. The morphology was investigated by X‐ray diffraction (XRD) and transmission electron microscopy (TEM). The composition of the fabricated fcc NiFe films ranged from 3 to 42 wt% Fe with a good adhesion. The as‐plated NiFe exhibited nanocrystalline grain sizes ranging from 12 to 18 nm with a coercivity as low as 16 A m−1. It was found that the grain size is generally higher at a lower iron content. However, pulse forward (PF) plating favours a refined grain size over DC plating which can be attributed to an increased nucleation rate caused by the high pulse current densities (high overpotential). By applying a thermal annealing for 2 h at 300 °C in a vacuum oven the coercivity of NiFe samples with ∼18.5 wt% Fe could be further reduced to 6 A m−1.